Linking migratory performance to breeding phenology and productivity in an Afro-Palearctic long-distance migrant - Joana S. Costa (Nature Portfolio, 2021)
Abstract Understanding the relationship between migratory performance and fitness is crucial for predicting population dynamics of migratory species. In this study, we used geolocators to explore migration performance (speed and duration of migratory movements, migratory timings) and its association with breeding phenology and productivity in an Afro-Palearctic insectivore, the European bee-eater (Merops apiaster), breeding in Iberian Peninsula. Bee-eaters migrated at higher travel speeds and had shorter travel duration in spring compared to autumn. Individuals that departed earlier or spent fewer days in-flight arrived earlier to the breeding areas. Our results show overall positive, but year-specific, linkages between arrival and laying dates. In one year, laying was earlier and productivity was higher, remaining constant throughout the season, while in the subsequent year productivity was lower and, importantly, declined with laying date. These results suggest that arriving earlier can be advantageous for bee-eaters, as in years when breeding conditions are favourable, early and late breeders produce high and similar number of fledglings, but when conditions are unfavourable only early breeders experience high productivity levels.